FEKTIFITA MEETODE CANTOL ROUDHOH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN BAGIANAK TUNAGRAHITA RINGAN - Riana Simbolon Kasiyati, Irdamurni (Universitas Negeri Padang, 2013)
The research was backgrounded by the problems found by the researcher on a child with a special need at a school for the children with disability, namely SDLB Negeri 20 Nan Balimo Solok. The children who have difficulty in reading, stringing letters into the right words, change word meaning to words that are not meaningful and eliminate, add and replace the letters that are not needed. The purpose of this research is to improve the reading ability of a starter child with modest mental retardation. This type of research is experimental research in the form of single subject research (SSR) using ABA design. Based on this research, the reading ability of the beginner of the child with modest mental retardation could be increased through the Cantol Roudhoh method. In the baseline condition (A1) is performed 10 times of meeting, at the first meeting, the aspects of intonation and sound tinny scored 40%, at the second meeting, the scores 10%, the 3rd - 5th meeting scores 20%, the 6th - 10th meeting, scores 10%.. On aspects of reading with correct pronunciation 1st - 10th meeting obtain scores 10%, on understanding aspects, 1st meeting obtain 20%, 2nd - 10th meeting, obtain scores 10%. In the intervention condition (B,) carried out for 11 times of meeting and the reading skills increases from the 11th meetings on the aspects of reading with the correct intonation and sound tinny scores 60%, the 12th scores 70%, the 12th - 13th scores 70%, the 14th - 21st meetingscores 100%.. On aspects of reading with correct pronunciation, the 11th meeting scores 30%, the 12th meeting scores ​​of 50%, the 13th meeting scores of 70%, the 14th meeting scores 80%, the 15th- 16th meeting scores 90, and the 17th - 20th meeting scores 100%. In the baseline condition (A2) is done 6 meetings, the 22nd meetings, the aspect of reading with the correct intonation and sound tinny scored 70%, the 23rd - 27th meeting, scores 100%, on aspects of reading with correct pronunciation meetings to 22 scored 30%, 23rd meeting scores 80%​​, the 24th - 27th meeting scores 100%. Thus the hypothesis (Ha) is acceptable, i.e. the Cantol Roudhoh method can be used to improve the child's ability to read for the beginning.